1993
DOI: 10.1007/bf01878355
|View full text |Cite
|
Sign up to set email alerts
|

In vivo anti inflammatory effects of the M20 IL-1 Inhibitor: I. Effects on acute inflammatory parameters

Abstract: Previous studies have described an IL-1 Inhibitor produced by a myelomonocytic line developed in our laboratory (Eur J Immunol 1986; 16: 1449). This IL-1 Inhibitor was secreted by the M20 line constitutively in addition to IL-1, from which it could be separated. We have recently shown that the M20 IL-1 Inhibitor is distinct from the IL-1ra. In vitro this factor inhibited IL-1 induced proliferative responses as well as PGE2 secretion by IL-1 induced fibroblasts. We also showed for the first time (Lymphokine Res… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
2
0

Year Published

1993
1993
1998
1998

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 21 publications
1
2
0
Order By: Relevance
“…Again, the IL-1 Inhibitor reversed this effect of IL-1, but not of IL-6 nor TNF. The specificity of the M20 Inhibitor to IL-1 was reported in vitro [15,19] and in vivo [21,22,23] and is also clear from this additional in vivo study. Additionally, we have shown that this Inhibitor effects proliferation (but not differentiation) of normal and leukemic blood cells [30].…”
Section: Il-1 Plays An Important Role In the Pathogenesis Of Many Dissupporting
confidence: 55%
See 2 more Smart Citations
“…Again, the IL-1 Inhibitor reversed this effect of IL-1, but not of IL-6 nor TNF. The specificity of the M20 Inhibitor to IL-1 was reported in vitro [15,19] and in vivo [21,22,23] and is also clear from this additional in vivo study. Additionally, we have shown that this Inhibitor effects proliferation (but not differentiation) of normal and leukemic blood cells [30].…”
Section: Il-1 Plays An Important Role In the Pathogenesis Of Many Dissupporting
confidence: 55%
“…In the first part of this study [23], we showed that IL-1 induced fever, leukocytosis and local inflammation, as measured by foot pad swelling and lymph node enlargement. These were all reduced significantly by the M20 IL-1 Inhibitor.…”
Section: Il-1 Plays An Important Role In the Pathogenesis Of Many Dismentioning
confidence: 99%
See 1 more Smart Citation